2018
DOI: 10.1021/acssuschemeng.7b02925
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Discoloration of Poly(vinyl alcohol)-Coated Paper Hydrophobized by Gas Grafting with Palmitoyl Chloride

Abstract: Gas grafting with fatty acid chloride (FAC) is a simple and ultrafast paper treatment, which produces only hydrochloric acid as a byproduct. In this study, poly­(vinyl alcohol) (PVOH)-coated paper was treated by gas grafting with palmitoyl chloride, and the effects of temperature, time, and concentration of palmitoyl chloride on discoloration were investigated. The grafting efficiency expressed by the water absorption capacity (Cobb size) and the amount of grafted FAC increased with increasing temperature, rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The discoloration is inevitable after exposure to high temperatures for an extended period of time. 30 Besides, it can be observed that no significant changes in the crystallinity are seen from the PXRD patterns measured after the 5th and 10th cycle (Fig. S8c, ESI †), thus considerably high values of toluene adsorption can still be observed after the 7th cycle towards the 10th cycle.…”
Section: Static State Voc Adsorptionmentioning
confidence: 92%
“…The discoloration is inevitable after exposure to high temperatures for an extended period of time. 30 Besides, it can be observed that no significant changes in the crystallinity are seen from the PXRD patterns measured after the 5th and 10th cycle (Fig. S8c, ESI †), thus considerably high values of toluene adsorption can still be observed after the 7th cycle towards the 10th cycle.…”
Section: Static State Voc Adsorptionmentioning
confidence: 92%
“…Its application to PVA material has been investigated and has shown an increase of the water repellency and a decrease of the water vapor transmission rate (Stinga & al., 2009;Schmid & al., 2012Schmid & al., & 2014Haas & al., 2017). The esteri cation reaction involved in the chromatogeny process leads to the production of gaseous hydrochloric acid as by-product, which in the case of PVA with high hydrolysis degree leads to a discoloration attributed to polyene formation (Lee & al., 2018(Lee & al., & 2023. It has been recently shown that hydrochloric acid was able to permeates PVA coating about 7g/m² (Lee & al., 2022).…”
Section: Introductionmentioning
confidence: 99%